Cervical Cancer and Human Papillomavirus Awareness among Women in Antigua and Barbuda - Prasanna Honnavar; Edmond Mansoor; Cherie Tulloch; Uttam Udayan; Isabella Cosmello; Purva Patel; Ashley Bersma (Medicina, 2023)
Background and objectives: Cervical cancer is the fourth leading cause of cancer-related deaths in women. Human papilloma virus (HPV) is known to cause cervical cancer. The incidence and mortality of cervical cancer has drastically reduced due to effective vaccination against HPV in developed countries. The projected rise in cervical cancer cases in Latin American and Caribbean countries necessitates a study to evaluate awareness about HPV, cervical cancer, the HPV vaccine, and prevention among women in Antigua and Barbuda. Materials and methods: This was an observational, cross-sectional study. The participants were women aged between 18 and 65 years, residing in Antigua and Barbuda. The study was conducted over the period of February to April 2023. After taking informed consent electronically, sociodemographic and behavioral data was collected through questionnaires sent out as links and QR-codes and were analyzed by QualtricsXM. The association between the demographic groups and awareness about HPV, cervical cancer, the HPV vaccine, and prevention was analyzed by a Chi-square test. Results: In total, 467 women were included in the study. The percentage of participants aware of HPV was 91.6% (n = 412). A total of 70.7% (n = 318) and 56.7% (n = 255) women were aware that cervical cancer is caused by HPV and is sexually transmitted, respectively. Although 70.6% (n = 315) of participants were aware that the vaccine protects against HPV, only 12.8% (n = 57) were vaccinated. Of the participants, 49.7% (n = 192) were willing to get vaccinated. The percentage of participants aware of the Papanicolaou (Pap) smear procedure was 98.9% (n = 435) and 87.8% (n = 382) had a Pap smear within the last 10 years while 12.2% (n = 53) never had a Pap smear screening. The willingness to know more information about HPV and the HPV vaccine among the participants was 77% (n = 335). Conclusions: The overall awareness among women in Antigua and Barbuda about HPV, cervical cancer, the HPV vaccine, and prevention was high. We recommend a national health education program and vaccine drive to complement our findings.